A single session of exercise increases connectivity in sensorimotor-related brain networks: a resting-state fMRI study in young healthy adults - Rajab, Ahmad S.; Crane, David E.; Middleton, Laura E.; Robertson, Andrew D.; Hampson, Michelle; MacIntosh, Bradley J. (Frontiers in Human Neuroscience, 2014)
Habitual long term physical activity is known to have beneficial cognitive, structural and neuro-protective brain effects, but to date there is limited knowledge on whether a single session of exercise can alter the brain’s functional connectivity, as assessed by resting-state fMRI (rs-fMRI). The primary objective of this study was to characterize potential session effects in resting state networks (RSNs). We examined the acute effects of exercise on the functional connectivity of young healthy adults (N=15) by collecting rs-fMRI before and after 20 minutes of moderate intensity aerobic exercise and compared this with a no-exercise control group (N=15). Data were analysed using independent component analysis, denoising and dual regression procedures. ROI-based group session effect statistics were calculated in RSNs of interest using voxel-wise permutation testing and Cohen’s D effect size. Group analysis in the exercising group data set revealed a session effect in sub-regions of three sensorimotor related areas: the pre and/or postcentral gyri, secondary somatosensory area and thalamus, characterized by increased co-activation after exercise (corrected p<0.05). Cohen’s D analysis also showed a significant effect of session in these three RSNs (p<0.05), corroborating the voxel-wise findings. Analyses of the no-exercise dataset produced no significant results, thereby providing support for the exercise findings and establishing the inherent test-retest reliability of the analysis pipeline on the RSNs of interest. This study establishes the feasibility of rs-fMRI to localize brain regions that are associated with acute exercise, as well as an analysis consideration to improve sensitivity to a session effect.